Effectiveness of Vision-Related Public Education Conferences - Labreche, Tammy; Irving, Elizabeth (Canadian Journal of Optometry, 2023)
Background: Trustworthy public education is required to ensure that Canadians receive the timely, consistent, and comprehensive eye care required to ensure optimal vision. The public education conference is one method to disseminate this information. The purpose of this study is to determine how effective this method is in achieving educational objectives. Methods: A pre-and post-survey was created and disseminated at a Center for Sight Enhancement hosted public education conference. The survey questions addressed perceived knowledge gained, attitudes regarding the presence of symptoms in eye disease and the importance of eye exams. Results: Of the 74 conference attendees, 27 completed the pre survey and 24 completed it post conference. There was a statistically significant increase in perceived knowledge gained in all conference areas. There was no statistically significant improvement in the awareness of the asymptomatic nature of early eye disease or the importance of eye examinations. Conclusion: Public education conferences are an effective method of eye care knowledge dissemination.